Neural correlates of mystical experience. (8th January 2016) - Cristofori, Irene; Bulbulia, Joseph; Shaver, John H.; Wilson, Marc; Krueger, Frank; Grafman, Jordan
Abstract: Mystical experiences, or subjectively believed encounters with a supernatural world, are widely reported across cultures and throughout human history. Previous theories speculate that executive brain functions underpin mystical experiences. To evaluate causal hypotheses, structural studies of brain lesion are required. Previous studies suffer from small samples or do not have valid measures of cognitive functioning prior to injury. We investigated mystical experience among participants from the Vietnam Head Injury Study and compared those who suffered penetrating traumatic brain injury (pTBI; n =116) with matched healthy controls (HC; n =32). Voxel-based lesion-symptom mapping analysis showed that lesions to frontal and temporal brain regions were linked with greater mystical experiences. Such regions included the dorsolateral prefrontal cortex (dlPFC) and middle/superior temporal cortex (TC). In a confirmatory analysis, we grouped pTBI patients by lesion location and compared mysticism experiences with the HC group. The dlPFC group presented markedly increased mysticism. Notably, longitudinal analysis of pre-injury data (correlating with general intelligence and executive performance) excludes explanations from individual differences. Our findings support previous speculation linking executive brain functions to mystical experiences, and reveal that executive functioning (dlPFC) causally contributes to the down-regulation of mystical experiences. Highlights: We investigated the causal role of brain region in mystical experience. VLSM showed increased mystical experience associated to ip temporal cortex and dlPFC. Patients with selective lesions to dlPFC reported increased mystical experience. Executive functioning contributes to the down-regulation of mystical experiences.